Randomized controlled trial of the CGRP receptor antagonist telcagepant for prevention of headache in women with perimenstrual migraine. (February 2016) - Ho, Tony W; Ho, Andrew P; Ge, Yang (Joy); Assaid, Christopher; Gottwald, Regina; MacGregor, E Anne; Mannix, Lisa K; van Oosterhout, Willebrordus PJ; Koppenhaver, Janelle; Lines, Christopher; Ferrari, Michel D; Michelson, David
Aim: The aim of this article is to evaluate the safety and efficacy of perimenstrual telcagepant, a CGRP receptor antagonist, for headache prophylaxis. Methods: We conducted a randomized, double-blind, placebo-controlled, six-month trial in women with migraine for ≥3 months who experienced perimenstrual headaches. Women were randomized to telcagepant 140 mg or placebo (2:1 ratio) for seven consecutive days perimenstrually. Safety was assessed by adverse events and laboratory tests. The primary efficacy endpoint was mean monthly headache days in the subset of women reporting perimenstrual migraine (−2 days to +3 days of menses onset) and ≥5 moderate or severe migraines per month prior to entering the trial. Results: Telcagepant was generally well tolerated: 66/2660 (2.5%) on telcagepant and 36/1326 (2.7%) on placebo discontinued because of a clinical adverse event. The percentages of patients with clinical adverse events, laboratory adverse events, or discontinuation because of a laboratory adverse event were also similar between treatments. Alanine aminotransferase elevations ≥3× normal occurred in 0.6% of women on telcagepant and 0.4% on placebo. Three women on telcagepant vs none on placebo had alanine aminotransferase elevations ≥8× normal. In the efficacy subset there was no significant effect of telcagepant ( n  = 887) vs placebo ( n  = 447) in mean monthly headache days (treatment difference −0.5 day (95% CI: −1.1, 0.1)). However, telcagepant was associated with a reduction in on-drug headache days (treatment difference −0.4 day (95% CI: –0.5, –0.2), nominal p  < 0.001). Conclusions: Telcagepant 140 mg taken perimenstrually for seven days was generally well tolerated, but was associated with transaminase elevations . Telcagepant did not reduce monthly headache frequency, but did reduce perimenstrual headaches.